FAKTOR-FAKTOR DETERMINAN EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH DI SMPN SUB RAYON 02 KABUPATEN SEMARANG - Cahyono, Wahyu (2011)
The purpose of this research is to analyze the influence of conflict work, basic ability, social relation to the effectiveness of principal leadership. The population of this research consistes of all of the teachers of SMP Negeri in the sub Rayon 02 Semarang regency with the total of the population 163 teachers. In order that the sample which was taken from the real representative population, in this research the researcher took the sample 116 teachers. The tool of the analysis that was used was double linier regression. The regression model that was used was OLS (Ordinary List Square).the statistic test that was used was model accurancy test (F test), guesing parameter accurancy test (T test), determination coefficient (R test). From the result of the analyze data shows that: (1) Particially there was significant influence conflict work towards effectiveness of principal leadership, t = 3,588; P. Value (sig) = 0,000, (2) Particially there was significant influence of basic ability towards effectiveness of principal leadership, t = 2,205; P. Value (sig) = 0,029, (3) Particially there was not significant influence social relation towards effectiveness of principal leadership, t = -0,650; P.Value (sig) = 0,517, (4) Simultaneusly there were conflict influence work, basic ability, and the social relationship by simulating towards effectiveness of principal leadership, or could be said that model in research is precise. The result of F test obtained by F= 16,213, with value significance value equal to 0,000, significant at 1%, (5) Determination Coefficient (R2 ) is 0,303 it mean that 30,3% independent variable could explain effectiveness of Principal leadership. The rest explained by other dissimilar variable is outside the model. (6) Effective Contribution of (EC) conflict work equal to 21,6%; basic ability equal to 12,7%, and the social relationship equal to -4,1%, so the total EC = 30,3%. The Result of classic assumption test indicates that regression model did not experience problem or classic deflect assumption (normality, linearity, multikolenierity, and heterokedastisity) so that is could be expressed by BLUE (Best, Linier, Unbiased, Estimator).